Does dutasteride have any cardioprotective effect in elderly men? A prospective randomised controled study (Annals of Medical Research, 2021)
Aim: To investigate whether the increased serum levels of testosterone secondary to Dutasteride therapy has any protective effect on cardiovascular system.Material and Methods: A prospective analysis of 50 patients diagnosed benign prostatic enlargement between May 2015 and May 2017 was performed. After randomization 25 patients treated with daily administration of 0.5 mg dutasteride (Dutasteride Group), and 25 patients were not given dutasteride (Control Group). We analyzed some serum novel cardiaovascular marker levels at baseline and after 6 months of the treatment. Echocardiography, carotid intima-media thickness and brachial artery resistive index (RI) were evaluated at baseline and after 6 months of the treatment.Statistical analyses were performed using SPSS, version 21. While “t test” was used for comparison the independent groups, paired t test was used in the matched groups. Statistical significance was considered at p0.05.Results: The differences in serum Lp a, hs-CRP and NT-proBNP levels were not statistically significant (p>0.05). Additionally, echocardiographic parameters, carotid intima-media thickness and brachial artery RI were similar before and after dutasteride tratment. Conclusion: After the short-term use of dutasteride, there was not a statistically significant difference in serum Lp a, hs-CRP and NT-proBNP levels. Additionally, echocardiographic parameters, carotid intima-media thickness and brachial artery RI were also similar.
Keywords: Dutasteride; cardioprotective effect; elderly men